MAPPING TOEFL PREDICTION SCORE RESULT BASED ON CEFR STANDARD AND TEST TAKERS’ PREPARATION PATTERN - Aritonang, Parjolo; Rijoly, Helena; Papasoka, Theofilia; Latuputty, Elyon; Rijoly, Qaranha; Matakupan, Azriel (Pattimura Excellence Journal of Language and Culture, 2023)
TOEFL Prediction score can also be seen as the benchmark of English Language Competence of the institution. This study looked into the types of preparation and the length of preparation and TOEFL Preparation Score result. The data were collected from 2 sources: online survey and the score compilation record from Pusat Studi Bahasa (PSB) Unpatti. There were 702 respondents to the survey which was distributed from November 9th to December 28th 2022. The respondents were TOEFL Prediction test-takers from Unpatti Ambon, PSDKU Aru, PSDKU MBD, and general Public. The result from the data analysis shows that 87.5% of test-taker have some sort of preparation before the test, the most common type of preparation is self-study (85,5%), and the most common length of preparation taken by test-takers is on average 1 week (70,5%). Lastly, overall test score indicated that majority of test takers (71.65%) were in A2 level and 26.64% were in A1 level based on CEFR. This suggested that 89.9% the graduates (test-takers) may be failing when competing in the world of job seeking and scholarship hunting.